Morphometric measurements of the fertile quail egg (Coturnix coturnix japonica) on chick weight at one-day old - Nuñez D., Jimny (2021)
The aim of this study was to relate morphometric measurements of the Coturnix coturnix japonica quail egg with the weight at birth in a commercial line of laying. In total, 274 birds were evaluated at one-day old, whose fertile eggs were classified into three categories according to weight: (1) 10.00-10.99, (2) 11.00-11.99, (3) 12.00-12.99 g for the variable birth weight, while the variables: transverse diameter and longitudinal diameter of the egg, and shape index were evaluated according to quartiles. In addition, the sex of the bird was evaluated. A completely randomized block model and correlations between the quantitative variables were used. A mean correlation of 0.65 was obtained between egg weight and longitudinal diameter, and low correlations between the variables longitudinal and transverse diameter (0.15). The birth weight was 7.36 ± 0.038, 7.92 ± 0.036 and 8.47 ± 0.058 g in categories 1, 2 and 3, respectively, and 7.83 ± 0.0672, 7.81 ± 0.0681, 7.69 ± 0.0665 and 7.85 ± 0.0682 g in quartiles 1, 2, 3 and 4, respectively. The egg shape index was 70.22 ± 0.321%. The weight of the male quail was 7.84 ± 0.0347 and in females it was 8.00 ± 0.0358 (p<0.05). The transverse and longitudinal diameter of the egg makes it possible to visually select a hatching egg, the transverse diameter being the most precise, since heavy quail at birth is not required.